Review Histology: A Text and Atlas: With Correlated Cell and Molecular Biology (Seventh, North American Edition) by Michael H. Ross PhD and Wojciech Pawlina MD Paperback: 992 pages Publisher: LWW; Seventh, North American Edition (January 19, 2015) - journal "Morphologia", Editorial office of (Морфологія / Morphologia / Morfologìâ, 2015)
The seventh edition of Histology: A Text and Atlas is ideal for medical, dental professions and students - cell biologists.